2014
DOI: 10.1038/srep06672
|View full text |Cite
|
Sign up to set email alerts
|

A less or more dusty future in the Northern Qinghai-Tibetan Plateau?

Abstract: Dust plays an important role in climate changes as it can alter atmospheric circulation, and global biogeochemical and hydrologic cycling. Many studies have investigated the relationship between dust and temperature in an attempt to predict whether global warming in coming decades to centuries can result in a less or more dusty future. However, dust and temperature changes have rarely been simultaneously reconstructed in the same record. Here we present a 1600-yr-long quantitative record of temperature and dus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 33 publications
1
33
1
1
Order By: Relevance
“…6A ). Independent temperature proxies are available for the past 1700 years based on annual varve thickness 49 and TEX 86 50 . All these three datasets were obtained from the same sediment core (5 m long), where no evidence of biodegradation was found over this short time interval 50 .…”
Section: Resultsmentioning
confidence: 99%
“…6A ). Independent temperature proxies are available for the past 1700 years based on annual varve thickness 49 and TEX 86 50 . All these three datasets were obtained from the same sediment core (5 m long), where no evidence of biodegradation was found over this short time interval 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The environment of Qinghai‐Tibetan Plateau (QTP) is highly sensitive to rapid global climatic variability owing to its large size, high altitude, and complex topography, as well as its unique bioclimatic position in relation to influences from Indian summer monsoon (ISM), Eastern Asian summer monsoon (EASM), and westerly circulation [e.g., Shen et al , ; An et al , ; H. Wang et al , ; Thomas et al , , ] (Figure ). Furthermore, it is likely that future climatic variability would be expected to be amplified on the QTP because of cloud‐ and snow‐albedo feedbacks [e.g., Diffenbaugh et al , ; Thomas et al , ] and would possibly have a profound effect on terrestrial ecosystems as well as human societies in the densely populated Eastern Asian continent [e.g., Liu et al , ; Fang et al , ]. As a result, the QTP has been notably invoked as an ideal research focus for paleoclimatologists and paleoecologists, with a variety of proxy records that have been derived from its multiple geological archives such as ice cores [e.g., Thompson et al , ; Du et al , ], lake sediments [e.g., Ji et al , ; Thomas et al , ], tree rings [e.g., Shao et al , ; B. Yang et al ., ], and peat sections [e.g., Hong et al , ; Zhao et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…5). In addition, the work of Liu et al (2014) from Kusai Lake has shown the RE is not constant. Although the varve counting indicates a stable sedimentation rate, the 14 C ages became older than the varve ages in the lower parts of the core, suggesting one RE is not enough to make use of the radiocarbon ages.…”
Section: Possibility Of Applying More Than One Re For Inorganic Carbomentioning
confidence: 97%
“…Age models established using radiocarbon dating of bulk organic matter or carbonate can be verified in a number of ways, e.g. by counting annual laminations if preserved in lake the sediments (Liu et al, 2014) or by dating TPR samples at the same or similar depths of the inorganic samples (Zhou et al, 2015). For the most recent sediments, 210 Pb ages can also be compared with the radiocarbon age model to provide verification.…”
Section: Validation Of the Chronologymentioning
confidence: 99%